Technological Discontinuities and Competitive Advantage: A Historical Perspective on Formula 1 Motor Racing 1950-2006 - Jenkins, Mark (Blackwell Publishing Ltd, 2010)
This paper considers the interplay between technological discontinuities and competitive performance. Much of the work on technological discontinuities has focused on macro levels of analysis such as industries and technologies rather than specific firms. This study uses a historical perspective on Formula 1 motor racing to explore the dynamics between firm level performance and technological discontinuities over a 57 year period. The study supports the findings of previous research that incumbent firms are often unable to adapt to the impact of exogenous shocks. However the study also reveals situations where a relatively small number of firms are able to sustain their competitive superiority through a number of successive discontinuities. I suggest that, in addition to dynamic capabilities, these firms possess sustaining capabilities – munificent resource configurations which extend the time available for firms to adapt to technological changes – thereby allowing them to remain competitive across discontinuities.
Keywords: MT=STRATEGY